ANALISIS PENGARUH ALOKASI DANA DESA, TINGAKAT PARTISIPASI ANGKATAN KERJA, PENDIDIKAN, DAN KESEHATAN TERHADAP TINGKAT KEMISKINAN PROVINSI LAMPUNG - Mayuza, Cici; Emalia, Zulfa (Bhinneka Multidisiplin Journal, 2026)
This study aims to analyze the effects of village funds, the labor force participation rate, and government expenditure in the education and health sectors on the poverty rate across 13 regencies in Lampung Province. The study uses data from 2015 to 2023. This research employs panel data analysis using the Random Effects Model (REM). The results indicate that village funds, the labor force participation rate, and government expenditure in the education sector have negative and significant effects on poverty. Meanwhile, government expenditure in the health sector does not have a significant effect on poverty.